Analysis of the Competitive Level Between Wadiah Yad Dhamanah Savings Products and Mudharabah Mutlaqah At PT. Bank Syariah Indonesia KCP Singkil Iskandar Muda - Dian Fajar Suryani; Muhammad Lathief Ilhamy Nasution (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Bank Syariah Indonesia kcp Singkil Iskandar Muda has a savings product using a contract between Wadiah Yad Dhamanah and Mudharabah Mutlaqah. Of course, both of these savings products have their advantages and disadvantages. As a result, indicators that affect the environment that are attracted to a competitive contract can be determined by various aspects, including aspects of return, aspects of costs, aspects of growth, social aspects, risk aspects, and promotion aspects. Therefore, the purpose of this study is to identify strengths and weaknesses, as well as indicators that affect savings products. This type of research is a qualitative research using analytical descriptive technique. Data collection was done by interview method. The subject of this research is leadership at PT. Bank Syariah Indonesia kcp Singkil Iskandar Muda. The results show that the Mudharabah mutlaqah savings product is more desirable than the wadiah yad dhamanah savings product because the indicator is substantially more profitable for customers.